On the floristic identity of Amazonian vegetation types. (24th March 2021) - Oliveira‐Filho, Ary T.; Dexter, Kyle G.; Pennington, R. Toby; Simon, Marcelo F.; Bueno, Marcelo L.; Neves, Danilo M.
Abstract: The Amazon forest is far from uniform, containing different forest types and even savannas, but quantitative analyses of this variation are lacking. Here, we applied ordination analyses to test the floristic differentiation among Amazonian vegetation types using data for virtually all known tree species occurring in the Amazon (8224), distributed across 1584 sites. We also performed multiple regressions to assess the role of climate and substrate in shaping continental‐scale patterns of community composition across Amazonia. We find that the traditional classification of Amazonian vegetation types is consistent with quantitative patterns of tree species composition. High elevation and the extremes of substrate‐related factors underpin the floristic segregation of environmentally "marginal" vegetation types and terra firme forests with climatic factors being relatively unimportant. These patterns hold at continental scales, with sites of similar vegetation types showing higher similarity between them regardless of geographic distance, which contrasts with the idea of large‐scale variation among geographic regions (e.g., between the Guiana Shield and southwestern Amazon) representing the dominant floristic pattern in the Amazon. In contrast to other tropical biomes in South America, including the Mata Atlântica (second largest rain forest biome in the neotropics), the main floristic units in the Amazon are not geographically separated, but are edaphically driven and spatially interdigitated across Amazonia. Two thirds of terra firme tree species are restricted to this vegetation type, while among marginal vegetation types, only white‐sand forests ( campinaranas ) have a substantial proportion of restricted species, with other vegetation types sharing large numbers of species. Abstract : We find that the traditional classification of Amazonian vegetation types is consistent with quantitative patterns of tree species composition. High elevations and the harshest extremes of substrate‐related factors underpin the floristic segregation of environmentally "marginal" vegetation types and terra firme forests with climatic factors being relatively unimportant. These patterns hold at continental‐scales, with sites of similar vegetation types showing higher similarity between them regardless of geographic distance, which contrasts with the idea of large‐scale variation among geographic regions (e.g., between the Guianan Shield and southwestern Amazon) representing the dominant floristic pattern in the Amazon. Two thirds of terra firme tree species are restricted to this vegetation type, while among marginal vegetation types, only white‐sand forests ( campinaranas ) have a substantial proportion of endemic species, with other vegetation types sharing large numbers of species.